The Influence of Democracy Index and Political Dynamics on Economic Growth in Indonesia During the Joko Widodo Administration - Lailatun Nuroniyah; Mellyna Mustika Rini; Mashudi (Penerbit Hellow Pustaka, 2025)
This research aims to analyze the influence of the democracy index and political dynamics on economic growth in Indonesia during the administration of President Joko Widodo. In this research, secondary data is used which includes the democracy index, political dynamics indicators, and Indonesian economic data for the 2014-2024 period. The results of the analysis show that although Indonesia has experienced an increase in the democracy index, political dynamic factors, such as political stability and public policy, have a significant role in influencing economic growth. Reducing levels of political polarization and progress in the quality of democracy contribute positively to economic stability. However, challenges in political policy and structural changes are factors that influence economic outcomes in a more complex way. This research concludes that the combination of democratic quality and stable political dynamics is the main key in creating sustainable economic growth in Indonesia.